ANALISIS YURIDIS TENTANG EKSISTENSI PENERAPAN HAK GUNA BANGUNAN DI KOTA BATAM - Permana, Oki Lukas; Svinarky, Irene (LPPM Universitas Putera Batam, 2023)
Problems regarding the Existence of the Application of Building Use Rights in Batam City are almost often not implemented properly and not in accordance with legal procedures. Basically, the use of Building Use Rights has been regulated in the Government Regulation of the Republic of Indonesia Number 40 of 1996 concerning Business Use Rights, Building Use Rights and Land Rights. However, in the implementation that is carried out there are still many that are not appropriate, there are still many governments and communities do not understand the use of Building Use Rights, how to obtain Building Use Rights. One of the factors or influences is the lack of government supervision, lack of socialization and the role of the government in ensuring the effectiveness and evaluation of the implementation of Building Use Rights. Therefore, the government needs to make efforts to improve the existence and effectiveness of the implementation of Building Use Rights in Batam City, such as conducting more intensive socialization to the community, increasing supervision of the use of Building Use Rights, and the active role of the Government in implementing Building Use Rights. This study aims to analyze the existence of the applicationof Right to Build (HGB) in Batam City in understanding how to obtain Right to Build and how the Right to Build can become a Right of Property in terms of applicable laws and regulations. The research method used is literature study and analysis of documents related to Building Use Rights in Batam City, sourced from journals, books, scientific papers, theses and other official documents.